Characteristics of sports events as a factor of increasing the efficiency of management in the scope of physical culture and sports - A. A. Talalaev (Путеводитель предпринимателя, 2020)
In order to improve the management ofthe scope of physical culture and sports, it is necessary to classify sports events both in terms ofanalyzing the existing laws and in terms of their consumer properties. The article also explores the phenomenon of «sport for all» and its distribution in the assessment ofthe development ofthe scope of sport.